Mental Wellbeing and Psychology : the Role of Art and History in Self Discovery and Creation. - Barker, Sue (Registered mental health nurse) (Advances in mental health research series., 2019)
Mental Wellbeing and Psychology unpacks the philosophical and psychological need to understand ourselves through an exploration of historical archives and artistic creativity. This focuses on some practical, evidence-based approaches to developing mental wellbeing. The book uses phenomenological psychology to explore the materials developed by the Stiwdio Arts group and offers an understanding of one's experiences of their world, recognising that these are embodied and perceived within a temporal and relational place. It offers examples for developing mental health and wellbeing interventions for charities, private care and the NHS. It provides an evidence base for the use of creativity and historical resources in mental health care. This book will be of great interest for academics, researchers and post-graduate students in the field of mental wellbeing, nursing and mentalhealth nursing, occupational therapy and social work.